A comparative evaluation of commercially available short fiber-reinforced composites - Sufyan Garoushi; Eija Säilynoja; Mark Frater; Filip Keulemans; Pekka K. Vallittu; Lippo Lassila (BMC Oral Health)
Abstract Background Short fiber-reinforced composites (SFRCs) are restorative materials for large cavities claimed to effectively resist crack propagation. This study aimed to compare the mechanical properties and physical characteristics of five commercially available SFRCS (Alert, Fibrafill Flow, Fibrafill Dentin, everX Flow, and everX Posterior) against a conventional particulate-filled composite (PFC, Essentia Universal). Methods The following characteristics were evaluated in accordance with ISO standards: flexural strength and modulus and fracture toughness. FTIR-spectrometry was used to calculate the degree of monomer conversion (DC%). The two-body wear test was performed in a ball-on-flat configuration using a chewing simulator with 15,000 cycles. A non-contact 3D optical profilometer was utilized to measure wear depth. The tensilometer method was used to quantify polymerization shrinkage-stress. Posterior composite crowns (n = 8) were made and quasi-statically loaded until fracture. The microstructure of the SFRCs were assessed using scanning electron microscopy. ANOVA was applied to statistically interpret the results, and then the post hoc Tukey’s analysis was performed. Results Among the evaluated composites, SFRC (everX Flow) had the lowermost wear depth (20.4 μm) and uppermost fracture toughness (2.8 MPa m1/2) values (p < 0.05). Fibrafill Flow (92 MPa) and Fibrafill Dentin (98 MPa) showed the lowest flexural strength values (p < 0.05). The used SFRCs exhibited equivalent values (p > 0.05) of shrinkage stress, except for everX Flow which had the highest value (5.3 MPa). everX Flow composite crowns presented significantly greater fracture resistance (3870 ± 260 N) (p < 0.05) than that of the other SFRCs tested. Conclusion Significant differences were found between the investigated characteristics of different commercially available SFRCs. It is noteworthy that certain SFRCs exhibited behavior comparable to that of conventional PFC, while others demonstrated superior performance.